Supplemental dietary Selenohomolanthionine affects growth and rumen bacterial population of Shaanbei white cashmere wether goats - Li, Long-Ping; Qu, Lei; Li, Tuo (Frontiers in Microbiology, 2022)
Selenium (Se) is an important trace element for all livestock growth. However, little is known about the dietary supplementation of Selenohomolanthionine (SeHLan) effect on growth and rumen microbiota of cashmere goats. In this study, thirty-two growing Shaanbei white cashmere wether goats with mean body weight (26.18 ± 2.71) kg were randomly assigned into 4 treatments, each with 8 replicates. The goats in 4 experimental groups were fed the basal diet (0.016 mg/kg Se) added with organic Se in the form of SeHLan, namely, control group (CG, added 0 mg/kg Se), low Se group (LSE, added 0.3 mg/kg Se), medium Se group (MSE, added 0.6 mg/kg Se), and high Se group (HSE, added 1.2 mg/kg Se). The feed experiment lasted for 70 days including 10-day adaptation, followed by 11 days digestibility trial including 7-day adaptation and 4-day collection period. On the last day of feeding experiment, rumen fluid was collected for microbial community analysis. The feed, orts, and fecal samples were collected for chemical analysis during digestibility trial. The results showed that average daily feed intake (ADFI) and the apparent digestibility of crude protein (CP) were both quadratic ally increased with increased SeHLan supply (Pquadratic < 0.05), while average daily gain (ADG) and feed conversion ratio (FCR) showed a linear response (Plinear < 0.05). The ADFI and ADG were all highest in the MSE group, which also had the lowest FCR (P < 0.05). Alpha diversity indices of the microbial community did not differ among four treatments. While principal coordinates analysis (PCoA) showed that rumen bacterial population differed among four groups. Taxonomic analysis revealed that Bacteroidetes, Firmicutes, and Euryarchaeota were the dominant phyla. The dominant families were Prevotellaceae, Selenomonadaceae, Methanobacteriaceae, and Bifidobacteriaceae. The significantly different rumen bacterial genera were found to be Methanobrevibacter, Quinella, Christensenellaceae_R-7_group, Veillonellaceae_UCG-001, and Succinivibrionaceae_UCG-002 (P < 0.05). In addition, Tax4fun analysis revealed that SeHLan supplemented groups enhanced the enrichment of genes related to energy metabolism, amino acid metabolism, carbohydrate metabolism, and enzymes. Twenty-eight pathways showed significant differences among four treatment groups (P < 0.05). In conclusion, dietary supplementation of medium SeHLan significantly affects rumen bacterial composition and ultimately promotes Shaanbei white cashmere wether goats nutrient digestibility and growth.